Amino-starch derivates for adsorption of specific pharmaceuticals and pesticides in contaminated water: Examination in both spiked and real water samples - Palić Nataša; Vukčević Marija; Maletić Marina; Mirković Miljana; Ristić Mirjana; Perić-Grujić Aleksandra; Trivunac Katarina (Journal of the Serbian Chemical Society)
In this study, the possibility of using modified potato starch, with nitrogen-containing chemical agents (melamine, cysteine and histidine) as green adsorbents for removing pharmaceuticals and pesticides from water has been investigated. The influence of additional modification of amino-starch with clay and diatomaceous earth was examined. The effect of the applied modification on the structural, surface and morphological properties was determined by FTIR, XRD and SEM analysis, while the adsorption properties were determined through the effectiveness of prepared materials to remove selected pollutants from spiked and real water samples. The efficiency of investigated amino–starches for the adsorption of pharmaceuticals and pesticides decreases in order: starch–histidine > starch–cysteine > starch–melamine, with a slightly better efficiency for pharmaceuticals adsorption. Additional modification of amino–starches with clay/diatomaceous earth did not contribute to the increase in adsorption efficiency. It was found that the influence of the matrix of real water samples on the adsorption efficiency is up to 10%, which represents a promising potential for applying amino–starch as a cheap and effective adsorbent for wastewater treatment. Also, starch–histidine and starch–cysteine showed the possibility of reusing up to three cycles of adsorption.